Impairments, Functional Limitations, and Access to Services And Education for Children with Cerebral Palsy in Uganda: A Population-Based Study - Andrews, Carin; Mwesige, Angelina Kakooza; Almeida, Rita; Peterson, Stefan Swartling; Mangen, Fred Wabwire; Eliasson, Ann-Christin; Forssberg, Hans (Developmental Medicine & Child Neurology, 2020)
To describe the functional limitations and associated impairments of children with cerebral palsy (CP) in rural Uganda, and care-seeking behaviour and access to assistive devices and education.Ninety-seven children with CP (42 females, 55 males; age range 2–17y) were identified in a three-stage population-based screening with subsequent medical examinations and functional assessments. Information on school and access to care was collected using questionnaires. The data were compared with Swedish and Australian cohorts of children with CP. We used the χ2 test and linear regression models to analyse differences between groups.Younger children were more severely impaired than older children. Two-fifths of the children had severe impairments in communication, about half had intellectual disability, and one third had seizures. Of 37 non-walking children, three had wheelchairs and none had walkers. No children had assistive devices for hearing, seeing, or communication. Care-seeking was low relating to lack of knowledge, insufficient finances, and ‘lost hope'. One-third of the children attended school. Ugandan children exhibited lower developmental trajectories of mobility and self-care than a Swedish cohort.The needs for children with CP in rural Uganda are not met, illustrated by low care-seeking, low access to assistive devices, and low school attendance. A lack of rehabilitation and stimulation probably contribute to the poor development of mobility and self-care skills. There is a need to develop and enhance locally available and affordable interventions for children with CP in Uganda.